Environmental Taxes. Its Influence on Solid Waste in Mexico - PRATS, Germán MARTÍNEZ; ÁLVAREZ GARCÍA, Yazmín Isolda; HERNÁNDEZ, Francisca SILVA; ZAMORA, Daniel TAGLE (Journal of Environmental Management and Tourism, 2020)
Globally occurs a series of transformations and natural dynamics connected with activities promoted by the human being in the environment. A situation of alteration in the stability is lived, which affects the local context with a regional, national and global scope. Solid waste pollution represents in Mexico a tax collection strategy in which environmental taxes, also known as green taxes, are applied. This article will describe and analyse the legal-fiscal instruments that are required to apply in Mexican environmental policy, visualizing the relevance of the solid wastes to generate the green taxes applied to them.